Doa Kasaro and its Cultural Codes in Muslim Society of Bima, Eastern Indonesia - Abdul Wahid (Ulumuna, 2019)
Dou Mbawa, an indigenous community as a small part of Bimanese Muslims, has a double minority identity since they have been sociologically and religiously considered as others. Having this character, they create a specific way of communication amongst themselves and between them and others through an annual ritual called Raju and Kasaro prayer. This article, using the hermeneutical and semiotical approach of interpretation, aims to discover a cultural interest in the Kasaro prayer. The Dou Mbawa not only positions the prayers as a form of spirituality but also utilizes it as a means of overcoming the problem concerning plurality, tensions, conflicts, and subordinations. This article illustrates the twisting of the politics of identity through Kasaro prayer. Beyond its function as a religious language, the Kasaro prayer carries a socio-cultural significance, yet politically meaningful as an ideology of resistance for the minority against the majority. The politics of identity adopted by the Dou Mbawa in Bima is symbolic. However, it implies the real struggle of a vulnerable-pluralistic society, mainly the struggle to maintain tradition, the consolidation of internal forces, and the imagination of multicultural societies. With this finding, this article offers a perspective on the formation of identity and dynamics of multiculturalism in Indonesia from the lense of spirituality.